Mapping drought risks in agriculture: a GIS and remote sensing study of Nagele Arsi district, Ethiopia - Ajitesh Singh Chandel (Cogent Food & Agriculture, 2025)
This study assesses agricultural drought vulnerability in Ethiopia’s Nagele Arsi district using integrated Geographic Information System (GIS) and remote sensing technologies. Covering a 30-year period (1992–2022), it employs a mixed-methods approach that combines satellite-derived indices—Normalized Difference Vegetation Index (NDVI), Vegetation Condition Index (VCI), and Standardized Precipitation Index (SPI)—with ground-based crop yield data. Results reveal significant correlations between NDVI (r = 0.71), VCI (r = 0.72), and SPI (r = 0.74) with crop yield anomalies, confirming the reliability of these indices for drought assessment. The analysis shows a rising trend in drought severity, with 2022 marked by extensive vegetative stress and rainfall deficits. A composite drought risk map indicates that 56% of the area faces severe drought risk, while 8.3% is categorized as very severe. Spatial patterns highlight higher vulnerability in the northern highlands, attributed to rainfall variability, elevation gradients, and land use intensity. The study underscores the importance of early warning systems, agro-ecological zoning, localized adaptation strategies, and integrated drought monitoring frameworks. Its findings offer actionable insights for policymakers and contribute to evidence-based planning aimed at improving drought resilience, ensuring sustainable agriculture, and enhancing food security in Ethiopia’s semi-arid regions.